The application of high purity diacylglycerol oil in whipped cream: effect on the emulsion properties and whipping characteristics. Issue 1 (1st January 2019) - Liu, Ning; Cui, Junjie; Li, Guanghui; Li, Daoming; Chang, Dawei; Li, Cheng; Chen, Xuefeng
ABSTRACT: The objective of this work was to examine the application of high purity diacylglycerol (DAG) oil in whipped cream as a partial substitute of hydrogenated palm kernel oil (HPKO). The DAG-enriched oil, with a purity of 94.50 wt%, was prepared via the enzymatic glycerolysis of palm oil/peanut oil blend and followed by molecular distillation. The substitute levels of 0, 10%, 20%, 30% and 40% (w/w) DAG for HPKO were employed, and the effects of DAG on emulsion properties, whipping characteristics and sensory quality were investigated. The result showed DAG oil promoted partial coalescence of fat globules in emulsion. As 0–20% DAG was involved in the emulsion, the average particle size ( d3, 2 ), surface protein concentration (SPC), partial coalescence of fat and overrun increased during whipping. The results of textural characteristics and sensory evaluation showed that 10-30% DAG substitute for HPKO would be successfully applied in whipped cream.